Profit Management in The Activities of An International Company - Jiayi Li; Damir Kudryakov (Communications of International Proceedings, 2022)
The global banking sector has undergone significant changes over several years, mostly due to the digitalization of both the environment and business. Today a bank is no longer only a financial services operator, but a platform for doing business. The variety of available technologies allows banking customers to switch to new ways of interacting with each other and with the business. Clients are using more and more channels for obtaining banking services, using new platforms to interact with banks. At the same time, technologies are being adapted to changes in human behavior, as a result of which more and more effective banking solutions are emerging for business development.a
Keywords: Keywords – information technology; profit; profit management; dumping; income; profitability; cost reduction; smartphones; viral promotion.